(untitled) (University of Khartoum Engineering Journal, 2022)
This work presents a generalized viscosity correlation for normal Alkanes (C2 to C20). The Arrhenius correlation is written in a generalized form by transforming their coefficients into fluid physical parameters of carbon number, normal boiling point temperature, critical temperature, critical pressure and accentric factor. Non parametric regression was used to develop the generalized correlation. It is validated using 245 data points covering normal Alkanes (C2 to C20). It reproduced the literature experimental data with absolute average percent deviation (AAPD) of less than 5 %. Arrhenius correlation yield similar level of accuracy. In conclusion the generalization is not made at the expense of accuracy.